2013
DOI: 10.1152/ajpgi.00140.2013
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y inhibits biliary hyperplasia of cholestatic rats by paracrine and autocrine mechanisms

Abstract: Biliary homeostasis is regulated by several factors through autocrine/paracrine signaling. NPY inhibits cholangiocarcinoma growth; however, no information exists regarding the autocrine/paracrine role of NPY on biliary hyperplasia during cholestasis. The aims of this study were to determine: 1) the expression of NPY and Y 1-Y5 in cholangiocytes and 2) the paracrine/autocrine effects of NPY on cholangiocyte proliferation. Normal or bile duct ligation (BDL) rats were treated with NPY, neutralizing anti-NPY antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Biliary proliferation was evaluated in formalin-fixed, paraffin-embedded liver sections (4–5 μm, 10 different fields analyzed from each sample from 3 different animals) by semi-quantitative immunohistochemistry for Ki-67 33 . We used q PCR to analyze PCNA, Bax, and cleaved Caspase-3 gene expression in RNA isolated from total liver, hHSC, and IMCL.…”
Section: Methodsmentioning
confidence: 99%
“…Biliary proliferation was evaluated in formalin-fixed, paraffin-embedded liver sections (4–5 μm, 10 different fields analyzed from each sample from 3 different animals) by semi-quantitative immunohistochemistry for Ki-67 33 . We used q PCR to analyze PCNA, Bax, and cleaved Caspase-3 gene expression in RNA isolated from total liver, hHSC, and IMCL.…”
Section: Methodsmentioning
confidence: 99%
“…The association between CCA and the hub genes NPY, LPAR1 , phospholipase A2 group IB, CPB1 , pancreatic lipase and KLF4 has not been widely reported. NPY expression has been shown to be upregulated in CCA (39,40), therefore regulating NPY expression may be beneficial for the treatment of CCA. Previous research demonstrated that KLF4 and microRNA-21 play a key role in mediating the EMT in CCA cells via the Akt/extracellular signal-regulated protein kinase 1 and 2 signaling pathway (41).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that neuropeptide Y (NPY) plays an important role in this process. Cholangiocytes express NPY receptors as well as secrete and respond to NPY during cholestasis with increasing proliferation 26 . Other neuroendocrine players that upregulate cholangiocyte proliferation include substance P, galanin, gonadotropin-releasing hormone (GnRH), and insulin-like growth factor 1 (IGF1) 12 , 27 , 28 .…”
Section: Discussion Of Recent Literaturementioning
confidence: 99%